Dietary artemisinin boosts intestinal immunity and healthy in fat greenling (Hexagrammos otakii) - Gu, Yixin; Wang, Wenjie; Zhan, Yu; Wei, Xiaoyan; Shi, Yanyan; Cui, Dandan; Peng, Tingting; Han, Jian; Li, Xuejie; Chen, Yan; Xue, Zhuang; Wang, Wei (Frontiers in Immunology, 2023)
Artemisinin (ART) is very common as a diet additive due to its immunoregulatory activities. Nonetheless, the immunoregulatory mechanism of ART on marine fish remains unknown. This study was conducted to comprehensively investigate the beneficial effects and explore the possible mechanism of ART ameliorating intestinal immune disease (IID) in fat greenling (Hexagrammos otakii).The targets of ART were screened by the Traditional Chinese Medicine Systems Pharmacology (TCMSP) database. Here, 8 putative targets of ART were collected and identified with Uniprot database and 1419 IID-associated target proteins were screened from the Drugbank, OMIM, Genecards and PHARMGKB Databases. The enrichment of Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway results showed that ART may have immunoprotect effects by regulating cellular responses to stress, hypoxia, inflammation and vascular endothelial growth factor stimulus through hypoxia-inducible factor 1 (HIF-1) signaling pathway.Molecular docking results showed that ART contains one active ingredient and three cross-targets which showed good binding with hypoxia-inducible factor 1-alpha (HIF1α), transcription factor p65 (RELA) and vascular endothelial growth factor A (VEGF-A), respectively. Further, an ART feeding model was established for assess the immunoprotect effect of ART on the intestine of H.otakii in vivo. The H.otakii fed ART diets showed smaller intestinal structural changes after being challenged by Edwardsiella tarda (E. tarda). Dietary ART significantly increased the activity of total superoxide dismutase, catalase, and glutathione peroxidase and decreased the content of malondialdehyde of H.otakii. Dietary ART significantly down-regulated the expression of transcription factor p65 (p65), hypoxia-inducible factor 1α (HIF1-α), vascular endothelial growth factor-A (VEGF-A), Cyclin D1, matrix metalloprotease 9 (MMP9), monocyte chemoattractant protein-1 (MCP-1), tumor necrosis factor-alpha (TNF-α) and interleukin-6 (IL-6) in the intestinal of H.otakii. The present results showed that diet with ART supplementation enhanced the organismal antioxidant capacity and immunity, optimized intestinal structure, and increased the resistance to E. tarda through SOD2/ nuclear-factor-kappa-B (NFκB)/HIF1-α/VEGF-A pathway in intestinal of H. otakii. This study explored the mechanism of ART on IID through the 3 combination of network pharmacology and experimental verification in vivo, which provides insight into the improve IID in H. otakii.